1978
DOI: 10.1111/j.1399-3054.1978.tb04100.x
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Transpiration and Water Uptake of Avena Plants

Abstract: The transpiration rate of oat plants, 6 days old, has been investigated. Dependent on the irradiance level of the white light used in the experiments, the transpiration rate oscillated with different period times. In darkness or at low irradiances the period was about 100–110 min. At higher irradiances the period was about 40 min. At intermediate irradiances autocorrelation analysis was used to find the period content of the transpiration rate. It was concluded that two oscillatory systems were present in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Stomatal cycling in the dark with a short and irregular period (less than 30 min), as exhibited by poplar, has previously been reported only by Stalfelt (1929). Longer cycles in the dark (1-2 h) have also been rarely observed (Ehrler 1971, Hopmans 1971, Klockare et al 1978. However, such behavior can be plausibly explained.…”
Section: Cycling In the Darkmentioning
confidence: 96%
See 1 more Smart Citation
“…Stomatal cycling in the dark with a short and irregular period (less than 30 min), as exhibited by poplar, has previously been reported only by Stalfelt (1929). Longer cycles in the dark (1-2 h) have also been rarely observed (Ehrler 1971, Hopmans 1971, Klockare et al 1978. However, such behavior can be plausibly explained.…”
Section: Cycling In the Darkmentioning
confidence: 96%
“…Oscillations of stomatal aperture occur in many plant species, even under constant environmental conditions. Oscillations have been observed commonly in the light (Barrs 1971, Cowan 1972, Lang et al 1969, Nagarajah 1978, Tyree and Cameron 1977, but rarely in the dark (Ehrler 1971, Klockare et al 1978, Stalfelt 1929. In most reported data, cycling is regular both in frequency and in amplitude, and there is generally good synchrony of stomatal movements among all the leaves of a plant (Cox 1968, Ehrler et al 1965, Lang et al 1969, Levy and Kaufman 1976.…”
Section: Introductionmentioning
confidence: 97%
“…The alternating pulse response was affected by increased ion concentration, particularly sodium ions. In the second study, again on Avena leaves, Klockare et al . (1978) found that when the light intensity was varied, a transition in the transpiration oscillation period occurred at a certain irradiance level.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have aimed at a systematic variation of the parameters of the water control system to search for period doubling sequences and possibly even more complicated curve forms. One attempt was made by Klockare et al . (1978) who varied the light intensity while recording the rhythmic behaviour of the transpiration.…”
Section: Introductionmentioning
confidence: 99%
“…This light intensity was high enough to maintain stomatal oscillations (cf. Klockare et al 1978). Cuttings were collected from several trees of the coastal plain of Israel.…”
Section: Materials and Methods Plant Materialsmentioning
confidence: 99%